An Explorative Study on Zakah Promotion Videos in Youtube Media: Content Analysis and User’s Interaction - Martini Dwi Pusparini; Nadia Anggarda Paramitha; Muhammad Lana Syifa’un Ni’ams (Falah: Jurnal Ekonomi Syariah, 2021)
Paying Zakah is compulsory for Muslims. However, it is still a vague issue among Indonesian Muslims. This study aims to an explore the zakah promotion videos in Youtube media to enhance Indonesian Muslims' awareness of zakah and analyzing users' interactions in this platform. This study was quantitatif using documantary approach with a content analysis approach to elaborate da'wah contents and Zakah outreach via social media. The study is in 6 months and analyzes contents and videos shared on YouTube with ten YouTube channels sample of population. The result found that the most popular channels that provide zakah outreach content is Al-Bahjah TV. While the most popular video is Panduan Zakah Fitrah (Guide to Zakah al-Fitr) by Yufid TV.  The videos on the fiqh of zakah in non-zakah agency channels provide higher positive impacts (98%), both in the forms of talks and motion graphics.